Prediction of cracking, yield and ultimate strengths based on the concrete three-phase micromechanics model. (30th December 2018) - Li, Dongqi; Li, Zongli; Yin, Yueming; Du, Xiangqin; Zhang, Guohui
Highlights: A micromechanics predictive model of the concrete strength was established. The Drucker-Prager criterion was adopted to decide the failure of the micro-phase. Cracking, yield and ultimate strengths were solved based on failure characteristics. Effectiveness and reliability of the model were verified by comparing with test data. Ultimate strength can increase by improving the elastic modulus of ITZ. Abstract: On a microscopic scale, concrete was regarded as a three-phase composite consisting of coarse aggregate, cement mortar and interface transition zone (ITZ). The coarse aggregates and their peripheral ITZ were equated with equivalent particles blended in cement mortar through two equivalent processes. Taking the effects of ITZ, aggregate gradation, maximum aggregate size and the interactions among equivalent particles into consideration, the average stress of microscopic phase of concrete was calculated based on a micromechanics model, and the stress concentration within ITZ phase was further solved. Adopting the Drucker-Prager criterion to decide the failure of the microscopic phases, the cracking strength, yield strength and ultimate strength of the concrete were calculated respectively when the ITZ cracking, the ITZ failure and the mortar failure occurred. The results were compared with test data to verify the effectiveness and reliability of the model. Based on the model, the influence of the elastic modulus of coarse aggregate, the coarse aggregate content and the elastic modulus of ITZ on the yield strength and ultimate strength are discussed. This paper presents an approach to explore the connection between macroscopic strength and microscopic phase strength, which provides a theoretical reference for studying the failure mechanism of concrete.